The Wiley-Blackwell Handbook of Childhood Cognitive Development / Second Edition - Goswami Usha (Wiley Blackwell, 2014)
An invaluable resource on the latest research and theories that shape our understanding of the crucial cognitive development of a child, from infancy to the onset of adolescence. Acknowledgements, Introduction, Infancy: The Origins of Cognitive Development, Social Cognition and Social Motivations in Infancy, Born to Categorize, Early Memory Development, Cognitive Development in Early Childhood, Language Development, Developing a Theory of Mind, Pretend Play and Cognitive Development, Topics in Cognitive Development in Childhood, Casual Reasoning and Explanation, The Development of Moral Reasoning, Children's Intuitive Physics, Reading Development and Dyslexia, Theories of Cognitive Development, Piaget's Theory: Past and Present and Future, Vygotsky and Psychology, Neuro Constructivism, Index.